'Gore is the world': embodying environmental risk in An Inconvenient Truth*. Issue 9 (2nd September 2019) - Lyons, James
Abstract: The challenge of constructing documentary films about environmental risk in order to 'change political understanding and promote action' is well recognized. Cinematic attempts to shock the public into action through images of future environmental catastrophe have been criticized for their counterproductive effect. This article looks closely at the most high-profile and commercially successful environmental risk documentary of all time, An Inconvenient Truth . Often dismissed as little more than a recording of former Vice-President Al Gore delivering a slide-show, closer inspection reveals a work that skilfully interweaves Gore's slide presentation with a narrative strand of personal recollection that creates a reflexive 'risk biography'. Adopting an interdisciplinary approach drawn from risk research, documentary scholarship and ideas of film performance, the article demonstrates how the film constructs Gore as a model of the risk-aware citizen exercising self-efficacy in the face of climate change. More subtly, the film employs a range of careful compositional and editing choices to shape and frame Gore's performance. The climatic becomes climactic in large part through the ways in which Gore embodies risk through his performance, with his voice, movements, gestures and other non-verbal cues combining with cinematic formal and narrative technique to convey the sense that he is, in effect, the vulnerable world incarnate.